Hybrid Condition Monitoring System for Power Transformer Fault Diagnosis - VARBAK NEŞE, SEÇİL; DURSUN, ERKAN (My University, 2023)
© 2023 by the authors.The important parts of a transformer, such as the core, windings, and insulation materials, are in the oil-filled tank. It is difficult to detect faults in these materials in a closed area. Dissolved Gas Analysis (DGA)-based fault diagnosis methods predict a fault that may occur in the transformer and take the necessary precautions before the fault grows. Although these fault diagnosis methods have an accuracy of over 95%, their validity is controversial since limited data are used in the studies. The success rates and reliability of fault diagnosis methods in transformers, one of the most important pieces of power systems equipment, should be increased. In this study, a hybrid fault diagnosis system is designed using DGA-based methods and Fuzzy Logic. A mathematical approach and support vector machines (SVMs) were used as decision-making methods in the hybrid fault diagnosis systems. The results of tests performed with 317 real fault data sets relating to transformers showed accuracy of 95.58% using a mathematical approach and 96.23% using SVMs.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarımda Enerji; Biyoyakıt Teknolojisi; Bilgi Sistemleri, Haberleşme ve Kontrol Mühendisliği; Kontrol ve Sistem Mühendisliği; Sinyal İşleme; İnşaat Mühendisliği; Yapı; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Energy in Agriculture; Biofuels Technology; Information Systems, Communication and Control Engineering; Control and System Engineering; Signal Processing; Civil Engineering; Structure; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; OTOMASYON & KONTROL SİSTEMLERİ; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; İNŞAAT VE YAPI TEKNOLOJİSİ; Engineering, Computing & Technology (ENG); ENGINEERING; AUTOMATION & CONTROL SYSTEMS; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; CONSTRUCTION & BUILDING TECHNOLOGY; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Fizik Bilimleri; Yapı ve inşaat; Yakıt Teknolojisi; Mühendislik (çeşitli); Enerji Mühendisliği ve Güç Teknolojisi; Enerji (çeşitli); Kontrol ve Optimizasyon; Elektrik ve Elektronik Mühendisliği; Renewable Energy, Sustainability and the Environment; Physical Sciences; Building and Construction; Fuel Technology; Engineering (miscellaneous); Energy Engineering and Power Technology; Energy (miscellaneous); Control and Optimization; Electrical and Electronic Engineering; dissolved gas analysis; fuzzy logic; hybrid; support vector machine; transformers